The relationship between learning style and career chosen by university students - Matalinares Calvet, María (2003)
The present study aimed to establish if learning styles related to the career chosen by university students. One thousand thirty six students, both male and female, aged 16 to 28, from different faculties of San Marcos National Major University were assessed with Kolb Inventory of Learning Styles. Outcomes show a systematic association among categories of learning style variable and some categories of career variable. This would mean that probability to study a defined career is not independent from learning style. Associations among sex and age variables and learning style were also found.